2023
DOI: 10.1007/s11270-023-06174-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Polymeric Materials on the Bacterial Attachment and Biofilm Formation in Anoxic Fixed-Bed Biofilm Reactors

Abstract: Six biofilm carriers with different polymer were studied in fixed-film systems under anoxic conditions. Different media of polymers influence wastewater treatment performance. The aim of this study was to investigate different polymeric materials, polyethylene terephthalate (PET), polyvinyl chloride (PVC), polypropylene (PP), high-density polyethylene (HDPE), and polymethyl methacrylate (acrylic), that affect bacterial attachment and biofilm formation in biofilm-based wastewater treatment technologies. Water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…As for the comparison of the elimination efficiency ammonia levels with previous studies can be seen in Table 7. Table 7 shows that the ammonia removal efficiency in this study was higher than Rajput and Khambete [26] but lower than Setiyawan et al [27]. The ammonia removal efficiency in this study was higher than Rajput and Khambete due to the microalgae used in the research.…”
Section: Influence On Time Stabili-zation and Number Of Cycles On Con...mentioning
confidence: 47%
See 1 more Smart Citation
“…As for the comparison of the elimination efficiency ammonia levels with previous studies can be seen in Table 7. Table 7 shows that the ammonia removal efficiency in this study was higher than Rajput and Khambete [26] but lower than Setiyawan et al [27]. The ammonia removal efficiency in this study was higher than Rajput and Khambete due to the microalgae used in the research.…”
Section: Influence On Time Stabili-zation and Number Of Cycles On Con...mentioning
confidence: 47%
“…Microalgae use ammonia for photosynthesis with the help of sunlight so that they can increase their biomass [32]. Ammonia removal efficiency in this study was lower than Setiyawan et al [27] because the MBBR used a contact time of seven days and the bio carrier used had a wider surface than Kaldness 1 (K1).…”
Section: Influence On Time Stabili-zation and Number Of Cycles On Con...mentioning
confidence: 63%
“…The wastewater treatment technology used is based on the formation of a biofilm on the surface of the packing elements of the bioreactor. The adhesion of microorganisms to the surface of the elements is crucial for the development of the biofilm [74]. The affinity of the surface of elements to the biofilm has an effect on the rate and degree of aggregation of microorganisms [20,75].…”
Section: Characteristics Of Packing Element Surfacementioning
confidence: 99%
“…Plastics with hydrophilicity or well-wetted properties tend to increase initial adhesion and enrich the biofilm's start-up, and polymers with hydrophilic properties have high surface energy [24]. Several studies showed PET possesses higher surface energy than PVC, PP, and HDPE [29,30,31]. In addition, PET plastic has properties that are quite flexible or easy to assemble and then form a structure.…”
Section: Comparison Of Removal Effectiveness Between Two Polymeric Me...mentioning
confidence: 99%